Feasibility of Intraocular Projection for Treatment of Intractable Corneal Opacity. Issue 4 (April 2019) - Shim, Sarah Y.; Gong, Songbin; Rosenblatt, Mark I.; Palanker, Daniel; Al-Qahtani, Ahmed; Sun, Michael G.; Zhou, Qiang; Kanu, Levi; Chau, Felix; Yu, Charles Q.
Abstract : Abstract: Despite many decades of research and development, corneal opacity remains a leading cause of reversible blindness worldwide. Corneal transplantation and keratoprosthesis can restore corneal clarity, but both have well-known limitations. High-resolution electronic microdisplays may offer an alternative to traditional methods of treating corneal disease using an intraocular implant to project imagery onto the retina, obviating the need for a clear cornea. In this study, we review previous work and recent technologic developments relevant to the development of such an intraocular projection system.